STRATEGIES FOR UTILIZING THE FACEBOOK APPLICATION IN INCREASING SALES OF MAR FASHION STORES IN TOLITOLI REGENCY: STRATEGI UNTUK MEMANFAATKAN APLIKASI FACEBOOK DALAM MENINGKATKAN PENJUALAN TOKO FASHION MAR DI KABUPATEN TOLITOLI - Angga Prayudha Ashari H. Mallu; Wahida Wahida; Yahya Yahya (International Journal of Economic Entrepreneurship and Business Management, 2025)
The results of this study aim to find out and analyze the Strategy of Utilizing the Facebook Application in Increasing Sales of Mar Fashion Stores in Tolitoli Regency. The method used in this study is a qualitative method. The subjects of this research are leaders, employees and consumers. The data sources used are primary data and secondary data. The data collection method carried out is by observation, interview and documentation methods. Then using SWOT analysis with IFAS and EFAS tests. The results of this study show that the Mar Fashion Store is located in square 1 by using an aggressive strategy. The strategy for utilizing the Facebook application in increasing sales used by Toko Mar Fashion is that growth strategies are often related to increasing the company's internal strengths, taking advantage of external opportunities, overcoming internal weaknesses and anticipating external threats. By ideizing and capitalizing on these opportunities, companies can expand the market, increase revenue to achieve increased business growth.